Comparative Analysis of α-Amylase Sequences in Selected Aspergillus Species and Analysis of Amylase Activity in Three Locally Isolated Aspergillus Species - Karen Hon, Jing Yi; Nurul Arrisya Aimi, Mohd Amran; Afiq Nasri, Abdullah; Ngieng, Ngui Sing; Hairul Azman, Roslan (Thammasat University, 2024)
Amylase is an important enzyme in industries where members of the Aspergillus genus are significant producers of industrial amylase enzymes; α- amylase is an endoamylase which plays a crucial role in starch hydrolysis. However, knowledge regarding the sequences and evolutionary relationship of α- amylase among sections Nigri, Flavi and Fumigati in the Aspergillus genus have remained unknown. The amylase activity of some previously isolated important Aspergillus species, namely A. niger, A. fumigatus and A. flavus, also requires further investigation. In this study, α- amylase sequences of species under three sections in the Aspergillus genus were retrieved from NCBI for sequence analysis and alignment for phylogenetic tree construction. The solid-based method was then applied to screen for amylase production and the Enzymatic Activity Index (EAI) was evaluated to analyze amylase activity. Similarities in enzyme sequences among the selected species were established through the presence of α- amylase domains and phylogenetic tree branching that rooted to a common ancestor. This study also found that the amylase activity of three selected species differed significantly, with A. flavus having the highest EAI of 1.03 ± 0.049, followed by A. niger (0.77 ± 0.049) and A. fumigatus (0.60 ± 0.103).